Peran Pondok Pesantren Modern Al-Habib Dalam Membina Karakter Remaja Di Kecamatan Sei Lepan Kabupaten Langkat - Melani, Ali Mukhlis (Pusdikra Publishing, 2022)
This research is a kind of qualitative research. Collecting data using the method of observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and conclusion research. Based on the results of this study, the role of Al-Habib Modern Islamic Boarding School in Fostering Youth Character in Sei Lepan District, Langkat Regency. Very good. The leader of the Islamic boarding school provides advice and services for adolescents in developing religious abilities, before carrying out this role the leader consults with Ustadz and Ustadzah at Islamic Boarding Schools. The conclusion of this study is the role of the Al-Habib Modern Islamic Boarding School in Fostering Youth Character in Sei Lepan District, Langkat Regency, namely the leader applies to Ustadz and Ustadzah on Sundays to come to the village to provide exercises such as praying, teaching the Koran and on Friday students -Santri are sent from Islamic boarding schools to villages around the Sei Lepan sub-district to become Friday preachers. Leaders train students in Islamic boarding schools to have good character so that they become good examples for the surrounding youth.